2000
DOI: 10.1136/pmj.76.893.160
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of adrenal aldosterone-producing adenoma

Abstract: SummaryConn's syndrome (adrenal aldosteroneproducing adenoma) and bilateral adrenal hyperplasia are the most common causes of primary aldosteronism. The treatment of choice for patients with aldosteroneproducing adenoma is unilateral total adrenalectomy. Recurrence after adequate surgery is exceptional. We present a patient with recurrence of an aldosterone-producing adenoma in the right adrenal gland 9 years after adenomectomy of a aldosterone-producing adenoma in the same adrenal gland. We conclude that aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…APAs virtually always remain benign, without local invasion or distant metastasis (9). Surgical removal ameliorates or cures hypertension in the large majority of patients (10). The mechanisms responsible for neoplasia and cell-autonomous aldosterone production are unknown.…”
mentioning
confidence: 99%
“…APAs virtually always remain benign, without local invasion or distant metastasis (9). Surgical removal ameliorates or cures hypertension in the large majority of patients (10). The mechanisms responsible for neoplasia and cell-autonomous aldosterone production are unknown.…”
mentioning
confidence: 99%
“…This approach would seem to be successful, although the postoperative long-term follow-up is often inadequate (5,7,14). Meanwhile, the recurrence of PA or CS following total or subtotal adrenalectomy has also been reported (3,(15)(16)(17). Therefore, knowledge of what lesions are present in the remaining cortices is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Shigematsu et al demonstrated multiple, highly active aldosterone production nodules, not only in unilateral adrenal hyperplasia, but also in adjacent tissues of APA (21). Even in the case of surgical treatment, CalvoRomero et al reported a case with recurrence in the ipsilateral adrenal gland after partial unilateral adrenalectomy (22). These findings suggest that patients with TAAE must be carefully followed up.…”
Section: Discussionmentioning
confidence: 99%